Peran Pendidikan Sains dalam Mengembangkan Kompetensi Abad 21 pada Sekolah Dasar - Maulida Arum Fitriana; I Wayan Suastra; Ida Bagus Putu Arnyana; I Made Citra Wibawa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to identify the role of science education in developing 21st-century competencies among elementary school students and to provide recommendations for more effective instructional implementation. The method used was a literature review by examining relevant scientific articles concerning the role of science education in fostering 21st-century competencies at the elementary school level. The research stages included designing the review, conducting the review, data abstraction and analysis, and organizing the review results. The data were obtained from articles that met predetermined inclusion and exclusion criteria. The results indicate that science education contributes to enhancing 21st-century skills through the utilization of digital media such as learning videos, YouTube, PowerPoint, Macromedia/Adobe Flash, digital comics, e-books, flipbooks, augmented reality (AR), virtual reality (VR), educational websites, educational television, and learning applications. Furthermore, the implementation of instructional models and approaches such as Problem Based Learning (PBL), inquiry, discovery learning, Science, Environment, Technology, and Society (SETS), Socio-Scientific Issues (SSI), and Science, Technology, Engineering, and Mathematics (STEM) supports the development of these competencies. In conclusion, science education at the elementary school level plays a strategic role in fostering 21st-century competencies through the integration of digital media and innovative learning models aligned with students’ needs. Keywords: 21st-Century Competencies, Elementary School, Science Education This study aims to identify the role of science education in developing 21st-century competencies among elementary school students and to provide recommendations for more effective instructional implementation. The method used was a literature review by examining relevant scientific articles concerning the role of science education in fostering 21st-century competencies at the elementary school level. The research stages included designing the review, conducting the review, data abstraction and analysis, and organizing the review results. The data were obtained from articles that met predetermined inclusion and exclusion criteria. The results indicate that science education contributes to enhancing 21st-century skills through the utilization of digital media such as learning videos, YouTube, PowerPoint, Macromedia/Adobe Flash, digital comics, e-books, flipbooks, augmented reality (AR), virtual reality (VR), educational websites, educational television, and learning applications. Furthermore, the implementation of instructional models and approaches such as Problem Based Learning (PBL), inquiry, discovery learning, Science, Environment, Technology, and Society (SETS), Socio-Scientific Issues (SSI), and Science, Technology, Engineering, and Mathematics (STEM) supports the development of these competencies. In conclusion, science education at the elementary school level plays a strategic role in fostering 21st-century competencies through the integration of digital media and innovative learning models aligned with students’ needs. Keywords: 21st-Century Competencies, Elementary School, Science Education